Crosstalk and Leakage Suppression by Mode Selectivity and Conversion in Terahertz Hybrid Metallo-Dielectric Waveguide Crossover and Intersections - Liu, Chun-Mei; Carignan, Louis-Philippe; Wu, Ke (IEEE transactions on microwave theory and techniques, 2024)
Hybrid metallo-dielectric waveguide (HMDW) crossover is proposed and presented in this work. Two parallel metal plates over two intersecting dielectric waveguide (DW) areas create a nonradiative dielectric (NRD) waveguide intersection that is harnessed to avoid the inherent radiation/leakage loss effect of such open DW discontinuities. Straight DW sections far from the intersection are set to minimize conductor loss free from any metal plates. Furthermore, crosstalk can be significantly reduced due to the mode conversion over the NRD waveguide intersection and the mode selectivity of the HMDW architecture. The proposed HMDW crossover has a lower structural insertion loss (material losses are excluded) of 0.37 dB from 275 to 295 GHz, whereas DW crossover and NRD crossover have 1.5 dB of insertion loss. The HMDW architecture is applied to a 10-mm back-to-back alumina-based waveguide with four orthogonal dielectric strips. The metal plates of NRD covering all intersections with a designed width can prevent the EM wave from propagating to four orthogonal dielectric strips. The fabricated prototype has a measured insertion loss of about 5.5 dB from 262 to 286 GHz (4.8 dB in simulation from 262 to 288 GHz). While the hybrid waveguide has a higher loss than its dielectric counterpart, it allows multiple orthogonal guides to cross-pass, providing an alternative solution for integrated systems where intersecting paths are inevitable. Its structural simplicity is beneficial to THz manufacturing.